KOMPARASI KUALITAS GURU DAN DUKUNGAN ADMINISTRATIF: STUDI PERBANDINGAN SEKOLAH DI DESA DAN DI KOTA - Hajrawati Ningsih (Universitas Muhammadiyah Surabaya, 2025)
A strong foundation can be created by high-quality education in order to achieve success and growth. Effective school management, such as the provision of athletic facilities, dining halls, and human resources, is a crucial element in raising teacher quality. Guru qualities should prioritize knowledge, gist, commitment to one's profession, and relationships with students. In contrast, administrative duties include overseeing the management of schools, ongoing projects, and available funds. The purpose of this study is to compare the quality of the teachers and administrative staff at schools based in cities and rural areas. To analyze differences and similarities between schools based in rural areas and those based in cities in terms of teacher quality and administrative support, the approach comparative method is used. Based on the results of the study, it is understood that the differences in guru quality between rural and urban schools are caused by two types of networks, namely managerial and academic networks. When creating high-quality and effective learning environments for students in rural and urban schools, a teacher's qualifications and administrative framework are crucial.